Amino Acids, Peptides, and Proteins: Implications for Nanotechnological Applications in Biosensing and Drug/Gene Delivery - Simge Er; Ushna Laraib; Rabia Arshad; Saman Sargazi; Abbas Rahdar; Sadanand Pandey; Vijay Kumar Thakur; Ana M. Díez-Pascual (Nanomaterials, 2021)
Over various scientific fields in biochemistry, amino acids have been highlighted in research works. Protein, peptide- and amino acid-based drug delivery systems have proficiently transformed nanotechnology via immense flexibility in their features for attaching various drug molecules and biodegradable polymers. In this regard, novel nanostructures including carbon nanotubes, electrospun carbon nanofibers, gold nanoislands, and metal-based nanoparticles have been introduced as nanosensors for accurate detection of these organic compounds. These nanostructures can bind the biological receptor to the sensor surface and increase the surface area of the working electrode, significantly enhancing the biosensor performance. Interestingly, protein-based nanocarriers have also emerged as useful drug and gene delivery platforms. This is important since, despite recent advancements, there are still biological barriers and other obstacles limiting gene and drug delivery efficacy. Currently available strategies for gene therapy are not cost-effective, and they do not deliver the genetic cargo effectively to target sites. With rapid advancements in nanotechnology, novel gene delivery systems are introduced as nonviral vectors such as protein, peptide, and amino acid-based nanostructures. These nano-based delivery platforms can be tailored into functional transformation using proteins and peptides ligands based nanocarriers, usually overexpressed in the specified diseases. The purpose of this review is to shed light on traditional and nanotechnology-based methods to detect amino acids, peptides, and proteins. Furthermore, new insights into the potential of amino protein-based nanoassemblies for targeted drug delivery or gene transfer are presented.